Changes in the prefrontal cortex after the hippocampus was injected with Aβ25-35 via the P35/P25-CDK5-Tau hyperphosphorylation signaling pathway. (10th January 2021) - Wang, Yiying; Sheng, Huajun; Zhao, Jing; Guo, Ling; Liu, Jianing; Xu, Jin; Liu, Qian; Huang, Juan; Jiang, Rong; Gan, Shengwei; Qiu, Guoping; Lu, Weitian; et al.
Highlights: There is evidence of prefrontal abnormalities in Alzheimer's disease, but the relationship to hippocampal damage is unknown. Injection of Aβ25−35 into the hippocampi lead to changes in the P35/P25-CDK5 pathway in the prefrontal cortex. This is one potential mechanism for prefrontal-mediated cognitive impairment and psychiatric symptoms of AD. Abstract: Alzheimer's disease (AD) is one of the common neurodegenerative illnesses in aging populations around the world. Recently, psychiatric symptoms are becoming increasingly important in recognizing the manifestations of AD in addition to cognitive impairment. Some studies suggest that the prefrontal cortex (PFC) is closely related to apathy/depression, and a network may exist between the CA1 of hippocampus and PFC. However, whether the injection of Aβ2535 into hippocampi may result in PFC abnormalities in AD model rats is unclear. In this study, it was investigated the changes in the PFCs after the hippocampal injection via the P35/P25 - Cyclin-dependent kinase5 (CDK5) - Tau hyperphosphorylation signaling pathway. Our results demonstrated that rats injected with Aβ25−35 showed decreased learning and memory ability, and increased depression-like behaviors compared with uninjected controls and saline-injected shams. P35/P25, CDK5, Tau[pS199], and Tau[pS202] are significantly elevated in the PFCs and hippocampi after Aβ25−35 was injected into the hippocampi. Furthermore, P35/P25-CDK5 complexes were detected in vivo by immunofluorescence and co-immunoprecipitation. Therefore, the relative expression of proteins associated with the P35/P25-CDK5 pathway showed the same changes in the hippocampi and PFCs after Aβ25−35 injection. These findings demonstrate a potential mechanism for prefrontal-mediated cognitive impairment and the psychiatric symptoms of AD.